HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TRIMESTER III TERHADAP SIKAP DALAM PERAWATAN TALI PUSAT DI PUSKESMAS BAAMANG I SAMPIT TAHUN 2019 - vina anggraini (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2020)
ABSTRACK Background : Neonatal tetanus is the most common cause of death in newborns baby and the handling of umbilical cord is not clean. The results of a preliminary study at the Baamang I Sampit Community Public Health were given the questions of knowledge and attitudes to 10 third trimester pregnant women, knowledge questions obtained by7 third trimester pregnant women well-known and 3 third trimester pregnant women have less knowledge. Meanwhile for demeanour questions, it was found that 6third trimester pregnant women positive and 4 third trimester pregnant women negative. Objective : Knowing Correlation of The Level Knowledge Pregnant Mother TM III On demeanourOf Umbilical Cord Tretament In Baamang I Public Health Center SampitYears 2019. Method : Research type isAnalytical research, with a Cross sectional research design and Accidental Samplingtechnique. The sampling used of in this research was a 30 samples. This research uses an instrument questionnaire. The location of this research in Baamang I Sampit Public Health. Result : The results of univariate analysis showed that the majority of knowledge of pregnant women third trimester about the method of umbilical cord treatment in good categories was 57%, namely 17 people and the majority of demeanour of pregnant women third trimester were positive 50.3%, that is 16 people. From the bivariate analysis, there was no relationship between knowledge of pregnant women third trimester on thedemeanour in umbilical cord treatment at in Baamang 1 Sampit Health because p value> 0.05 (p value = 0,878). Conclusion : There is a not significant correlation between level knowledge pregnant mother third trimester and demeanour of umbilical cord treatment.Keyword : Knowledge, Demeanour, Umbilical Cord Treatment, Third Trimester Pregnant Women